2004
DOI: 10.1161/01.atv.0000119353.03690.22
|View full text |Cite
|
Sign up to set email alerts
|

Human Apolipoprotein A-IV Reduces Secretion of Proinflammatory Cytokines and Atherosclerotic Effects of a Chronic Infection Mimicked by Lipopolysaccharide

Abstract: Objective— Expression of human apolipoprotein (h-apo) A-IV in apoE-deficient (apoE 0 ) mice (h-apoA-IV/E 0 ) reduces susceptibility to atherosclerosis. Chronic infection mimicked by exposure to lipopolysaccharide (LPS) increases the size of atherosclerosis lesions in apoE 0 mice. Thus, we used h-apoA-IV/E 0 mice to determine whether h-apoA-IV plays a protective role after LPS administration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
71
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 27 publications
(20 reference statements)
8
71
1
1
Order By: Relevance
“…It has also been reported that HDL-associated apoJ can inhibit LDL oxidation by artery wall cells ( 64 ). In addition, apoA-IV has been demonstrated to exert anti-oxidant, anti-infl ammatory, and anti-atherosclerotic actions in vivo (65)(66)(67).…”
Section: Downloaded Frommentioning
confidence: 99%
“…It has also been reported that HDL-associated apoJ can inhibit LDL oxidation by artery wall cells ( 64 ). In addition, apoA-IV has been demonstrated to exert anti-oxidant, anti-infl ammatory, and anti-atherosclerotic actions in vivo (65)(66)(67).…”
Section: Downloaded Frommentioning
confidence: 99%
“…In contrast, apoE4 has been suggested to be proinflammatory (Ophir et al 2005). Another HDL-associated protein, apoA-IV, showed anti-atherosclerotic, antiinflammatory, and antioxidant actions in vivo (Ostos et al 2001;Recalde et al 2004;Vowinkel et al 2004). In addition, apoJ, also called clusterin, has been reported to block LDL oxidation by artery wall cells (Navab et al 1997).…”
Section: Mechanisms Under Physiological Conditionsmentioning
confidence: 99%
“…LPS mimics chronic infection and increases the atherosclerotic lesion in Apoe -deficient mice. However, in APOA4/Apoe Ϫ / Ϫ mice, lesion size was reduced and proinflammatory cytokine production was lower, although autoantibodies to oxidized LDL (OX-LDL) were higher (17). These studies provide additional insight into the anti-inflammatory, antiatherogenic role of apoA-IV.…”
mentioning
confidence: 93%
“…Further, these mice had reduced oxidative markers, including aldehyde-modified LDL, suggesting an antioxidant effect of apoA-IV (16), although this, per se, does not prove that the antiatherogenic effect of apoA-IV is a result of antioxidant potential. More recently, the protective effect of the human APOA4 transgene in APOA4/ Apoe Ϫ / Ϫ mice was examined in relation to lipopolysaccharide (LPS) exposure (17). LPS mimics chronic infection and increases the atherosclerotic lesion in Apoe -deficient mice.…”
mentioning
confidence: 99%